1999
DOI: 10.1017/s0960258599000185
|View full text |Cite
|
Sign up to set email alerts
|

The effect of light and number of diurnal temperature fluctuations on germination of Phragmites australis

Abstract: Seed germination of the wetland emergent perennial Phragmites australis is stimulated by diurnally fluctuating temperatures. A germination experiment in darkness and light at different temperature regimes showed that P. australis germinated as well in darkness as in light over most of the temperature regimes tested. The germination requirements could partly explain why this species, despite a large annual production of small seeds, does not accumulate a persistent soil seed bank. A second experiment examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 27 publications
0
28
0
3
Order By: Relevance
“…Several authors have reported the importance of temperature during seed development and maturation as an important factor affecting seed germination (Allen & Meyer, 2002). Ekstam et al (1999) have elucidated the importance of fluctuating temperature as a requirement for germination and that in addition to being a sensor for ΄exposed΄ seed sites, it is also effective as a germination timing sensor. A slight increase or drop in temperature may affect a number of processes determining the germinability of seeds, including membrane permeability, activity of membrane-bound proteins and cytosol enzymes (Bewley & Black, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported the importance of temperature during seed development and maturation as an important factor affecting seed germination (Allen & Meyer, 2002). Ekstam et al (1999) have elucidated the importance of fluctuating temperature as a requirement for germination and that in addition to being a sensor for ΄exposed΄ seed sites, it is also effective as a germination timing sensor. A slight increase or drop in temperature may affect a number of processes determining the germinability of seeds, including membrane permeability, activity of membrane-bound proteins and cytosol enzymes (Bewley & Black, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Available studies of seedling establishment of emergent macrophytes indicate that wet bare bottoms represent the best conditions, combining wet, but not flooded substrate, and light indicating space free of competition (Hejný and Husák, 1978;Weisner and Ekstam, 1993;Ekstam et al, 1999). Accordingly, the middle eulitoral with only a partial cover of perennial emergent macrophytes offers the best space for seedling establishment.…”
Section: Limits To Generative Dispersalmentioning
confidence: 99%
“…Em geral, a alternância de temperatura é um mecanismo importante para aquelas espécies que não possuem sementes que germinam sob temperatura constante, revelando capacidade de adaptação e sucesso no estabelecimento, no ambiente que ocorrem (Ekstam et al 1999;Abdo & Paula 2006;Simão & Takaki 2008).…”
Section: Discussionunclassified
“…Para Abdo & Paula (2006), as temperaturas alternadas de 20-30 e de 25-35 °C favorecem o processo germinativo de sementes de Croton floribundus e não há germinação a 15, 20 e 40 C ou essa é mínima a 25 °C. Ekstam et al (1999) mostraram que sementes de Phragmites australis apresentaram alta porcentagem de germinação em temperaturas alternadas, na presença e ausência de luz.…”
Section: Discussionunclassified
See 1 more Smart Citation